An Examination of Undergraduate Student Citation Behavior - Carlson, Jake (The Journal of academic librarianship, 2006)
Using data collected from 583 bibliographies from student research papers, this study analyzes the effect that the class year of the student, the academic discipline of the course, and the level of the course have on the type and the mean number of sources cited by undergraduates. All three variables had some significant effects on student citation behavior. Additional analysis was done to pinpoint which variable was likely to be the primary cause of the observed effects.